The Economisation of Climate Change - Skovgaard, Jakob (Cambridge University Press, 2022)
International economic institutions economise climate change, treating it as an economic rather than environmental issue. This book explores how three such institutions - G20, IMF, OECD - have addressed climate finance and fossil fuel subsidies, and the consequences of the economisation of climate change. Also available as Open Access.